Determinanty kształtowania polskiego bezpieczeństwa gospodarczego. Wybrane aspekty - Jaźwiński, Ireneusz (Przegląd Strategiczny, 2011)
Condition for the development of modern states and societies is appropriate shaping of economic security. Effectiveness and efficiency of economic security development depend largely on the rational identification and use of many determinants variable in space and time This article introduces some selected aspects of theoretical and practical issues of determinants of Polish economic security shaping. The essence of economic security is described. The paper presents the concept and types of determinants of the security in theoretical approach, including own proposed classification of the economic security determinants. Attention is drawn at the macroeconomic determinants of Polish economic security. The results of the National Programme Foresight Poland 2020 is analysed in terms of the determinants of Polish economic security shaping. Provisions of the National Security Strategy of the Republic of Poland on economic security are presented.